Water Management Challenges in Mega Deltas – The Case of Bangladesh - Salahuddin, Ahmad (2023)
An abstract of a research on the water management challenges in the delta regions of Bangladesh. This study is presented during the 2023 International Rice Congress in Manila, Philippines.